2011
DOI: 10.1007/s10096-011-1216-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mumps virus-specific antibodies by different serological assays: which test correlates best with mumps immunity?

Abstract: Mumps is one of the vaccine-preventable childhood diseases and it has not yet been eradicated in Germany. This raises the question as to whether the available mumps vaccines are effective enough to prevent mumps and which antibody test system allows the authentic assigning of mumps-specific immunity. In an attempt to answer this question, we analysed 227 sera samples from medical students of the University Hospital Frankfurt/Main, Germany, using different test systems: indirect immune fluorescence, neutralisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
1
13
0
7
Order By: Relevance
“…Although neutralizing antibody is thought to be essential for protection (40) and PRN titration is generally considered to be the gold standard for mumps serology, previous attempts to determine a reliable threshold for protective PRN titers have been unsuccessful (20). To add further ambiguity, there have been several reports of poor correlations between mumps PRN titration and various other serologic methods, such as ELISA and immunofluorescent assays (IFA) (25)(26)(27)(28)(29)(30)(31)(32)(33)(34). These studies indicated that mumps serologic data must be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although neutralizing antibody is thought to be essential for protection (40) and PRN titration is generally considered to be the gold standard for mumps serology, previous attempts to determine a reliable threshold for protective PRN titers have been unsuccessful (20). To add further ambiguity, there have been several reports of poor correlations between mumps PRN titration and various other serologic methods, such as ELISA and immunofluorescent assays (IFA) (25)(26)(27)(28)(29)(30)(31)(32)(33)(34). These studies indicated that mumps serologic data must be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have indicated that mumps-neutralizing antibody does not correlate particularly well with mumps IgG ELISA measurements (25)(26)(27)(28)(29)(30)(31)(32)(33). An explanation for these observations is that mumps antibodies predominantly measured by ELISAs which use whole-virus antigen differ from those measured by plaque neutralization tests.…”
Section: Mumps Igg Elisa Prn Titer Pre-and Post-mmr Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the correlation of serological test results and clinical protection is particularly poor in mumps vaccination [11,25,26], two types of tests were used in this study : the HI test and the plaque reduction neutralization test (PRNT). Genotyping based on the SH (presented above), although informative, cannot lead to a conclusion on the cross-reactive potential between different mumps viruses.…”
Section: Analyses Of the Mumps Virus Neutralizing Antibodies In Guinementioning
confidence: 99%
“…However, no correlation could be found between mumps seroprevalence and the likelihood of outbreaks. Several studies have brought into question whether measuring antibody levels following vaccination is an effective method of assessing resistance to vaccine-preventable viral infections (12,20), against which a cell-mediated immunity response appears to provide protection in addition to humoral immunity (14,21). It should be noted, however, that there does seem to be some correlation between levels of humoral antibody and the ability to resist infection (13).…”
Section: Discussionmentioning
confidence: 99%